Radiographic and Arthroscopic Assessment of DRUJ Instability Due to Foveal Avulsion of the Radioulnar Ligament in Distal Radius Fractures - Nakamura, Toshiyasu; Iwamoto, Takuji; Matsumura, Noboru; Sato, Kazuki; Toyama, Yoshiaki (Journal of Wrist Surgery, 2014)
Background As the triangular fibrocartilage complex (TFCC) anchors the distal radius to the ulna via the radioulnar ligament (RUL), a severely displaced distal fragment of the radius may be associated with a foveal avulsion of the TFCC. The purpose of this retrospective study was to assess, radiographically and arthroscopically, the relationship between displacement of the radius, the ulnar styloid, and avulsion of the RUL resulting in distal radioulnar joint (DRUJ) instability.Materials and Methods Twenty-nine wrists of 29 patients with intra- and extra-articular distal radius fractures/malunion who underwent reduction or a corrective osteotomy of the displaced/malunited fracture, and/or wrist arthroscopy, were assessed radiographically and arthroscopically. Radial translation, radial inclination, radial shortening, volar or dorsal tilt, and the presence of an ulnar styloid fracture with more than 4 mm of displacement were measured from the initial films. Radiocarpal arthroscopy was used to assess peripheral lesions of the TFCC, while DRUJ arthroscopy was used to assess the foveal attachment. The relationship between displacement of the distal radius or the ulnar styloid fracture and the TFCC injury, including avulsion of the RUL, was recorded.Results Univariate analysis revealed that increased radial translation, decreased radial inclination, increased radial shortening, and an ulnar styloid fragment radially displaced by more than 4 mm were significant predictors of RUL avulsion at the fovea. Volar or dorsal tilt of the radius and ulnar variance did not correlate with RUL avulsion or TFCC injuries. Multiple logistic regression analysis revealed that radial translation was an independent risk factor of foveal avulsion of the RUL.Conclusions Increased radial translation and radial shortening and decreased radial inclination of the distal fragment can be associated with a foveal avulsion of the RUL. Radial translation can be an independent risk factor of foveal avulsion of the RUL.
Keywords: distal radius fracture; radial translation; triangular fibrocartilage complex; radioulnar ligament